Natural Interaction With Robots, Knowbots and Smartphones 2013
DOI: 10.1007/978-1-4614-8280-2_28
|View full text |Cite
|
Sign up to set email alerts
|

FLoReS: A Forward Looking, Reward Seeking, Dialogue Manager

Abstract: We present FLoReS, a new information-state based dialogue manager, making use of forward inference, local dialogue structure, and plan operators representing sub-dialogue structure. The aim is to support both advanced, flexible, mixed initiative interaction and efficient policy creation by domain experts. The dialogue manager has been used for two characters in the SimCoach project, and is currently being used in several related projects. We present the design of the dialogue manager and preliminary comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Finally, in the dialogue below, apart from the fact that I+S cannot represent utterance (1), question ( 2) is answered with a subdialogue starting at question (3) that shifts the dialogue initiative (Bohus and Rudnicky, 2002;Horvitz, 2007;Litman and Allen, 1987;Morbini et al, 2012). In utterances ( 4) and ( 6), the system is proposing a value and in ( 5) and ( 7), the user is rejecting or accepting the proposal.…”
Section: Mixed Initiative and Collaborationmentioning
confidence: 99%
“…Finally, in the dialogue below, apart from the fact that I+S cannot represent utterance (1), question ( 2) is answered with a subdialogue starting at question (3) that shifts the dialogue initiative (Bohus and Rudnicky, 2002;Horvitz, 2007;Litman and Allen, 1987;Morbini et al, 2012). In utterances ( 4) and ( 6), the system is proposing a value and in ( 5) and ( 7), the user is rejecting or accepting the proposal.…”
Section: Mixed Initiative and Collaborationmentioning
confidence: 99%
“…The study used 4 trained Natural Language Understanding (NLU) classifiers, each of which: identifies generic dialogue act types, assigns positive or negative valence to the user input, supports domain-specific small talk, and identifies domain-specific dialogue acts. The dialogue policy the study implemented used the FloReS (3) dialogue manager. The researchers conducted an experiment and the results showed that the users were comfortable in sharing information with SimSensei, giving the impression that virtual human agent are effective in extracting information from its users.…”
Section: + Both Authors Have Equal Contributionmentioning
confidence: 99%
“…For natural language understanding, generation, and dialogue management, we built on top of the FLoRes system (Morbini et al 2012). This system allowed us to define the information state for employees and attributes and a set of policies for prompting and responding to the user.…”
Section: Related Workmentioning
confidence: 99%